2012
DOI: 10.1186/1750-0680-7-11
|View full text |Cite
|
Sign up to set email alerts
|

Revaluing unmanaged forests for climate change mitigation

Abstract: BackgroundUnmanaged or old-growth forests are of paramount importance for carbon sequestration and thus for the mitigation of climate change among further implications, e.g. biodiversity aspects. Still, the importance of those forests for climate change mitigation compared to managed forests is under controversial debate. We evaluate the adequacy of referring to CO2 flux measurements alone and include external impacts on growth (nitrogen immissions, increasing temperatures, CO2 enrichment, changed precipitatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 40 publications
1
13
0
Order By: Relevance
“…According to the results the unmanaged forests provided only limited possibilities for climate change mitigation compared to the possibilities to store carbon in wood based materials and to substitute materials and fuels in energy production. Our results support earlier studies (Klein et al 2013, Krug et al 2012 and indicated that drawing a system boundary excluding carbon storage and substitution effects of harvested biomass may produce variable results as seen, for example in Naudts et al (2016).…”
Section: Discussionsupporting
confidence: 90%
“…According to the results the unmanaged forests provided only limited possibilities for climate change mitigation compared to the possibilities to store carbon in wood based materials and to substitute materials and fuels in energy production. Our results support earlier studies (Klein et al 2013, Krug et al 2012 and indicated that drawing a system boundary excluding carbon storage and substitution effects of harvested biomass may produce variable results as seen, for example in Naudts et al (2016).…”
Section: Discussionsupporting
confidence: 90%
“…This is especially difficult in uneven-aged forest stands. On top of this, common yield tables tend to be outdated since additional impacts, like an enhanced CO 2 concentration, nitrogen (N) depositions, and changed precipitation and temperature patterns, have initiated increased growth rates [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Further, most discussions do not differentiate between direct human-induced and other human-induced impacts, like increased concentrations of CO 2 or increased N deposition, a prolonged vegetation period, or changed precipitation rates. Those indirect human-induced impacts also lead to increased forest growth but cannot be attributed to forest management practices, as the impacts affect managed as well as unmanaged forest [6]. Since it is quite difficult, if possible at all, to determine the effect of such "other" human-induced impacts than management, only a direct comparison of managed and unmanaged forests can allow a conclusion on the impact of management on superior biomass development and, from this, the impact on carbon sequestration.…”
Section: Introductionmentioning
confidence: 99%
“…In the study in [17], the land-use system and altitude were shown to be important factors in the regulation of SOM decomposition by altering the natural soil characteristics. Unmanaged or old-growth forests are important for carbon sequestration [18].…”
Section: Introductionmentioning
confidence: 99%